Poverty orderings and indexes: An application for Mexico - Lustig, Nora (Estudios Económicos de El Colegio de México, 1991)
This paper uses Atkinson's and Fosterand Shorrocks's approach to generate poverty orderings for different population groups in Mexico. The poverty is measured using a range of poverty lines valued from zero to an arbitrary maximum. Poverty is estimated using three poverty measures: the head-count ratio, the normalized poverty gap, and the Foster et al. P 3 index. For the comparisons undertaken here the head-count ratio yields an unambiguous ordering.